Breast Cancer Screening in Women Exposed In Utero to Diethylstilbestrol - Camp, Elizabeth A. (Mary Ann Liebert, Inc., 2009)
PURPOSE: To determine if women exposed in utero to diethylstilbestrol (DES) are more likely than unexposed women to receive recommended or additional breast cancer screening examinations. METHODS: 1994 Diethylstilbestrol-Adenosis (DESAD) cohort data are used to assess the degree of recommended compliance of breast cancer screenings found in 3140 DES-exposed and 826 unexposed women. Participants were enrolled at four sites: Houston, Boston, Rochester, and Los Angeles. Logistic regression modeling was used to analyze mailed questionnaire data that included reported frequency over the preceding 5 years (1990–1994) of breast-self examinations (BSEs), clinical breast examinations (CBEs), and mammograms. RESULTS: DES-exposed women exceeded annual recommendations for CBEs (aOR 2.20, 95% CI, 1.04-4.67) among women without a history of benign breast disease (BBD) compared with unexposed women. There were no other statistically significant differences between exposed and unexposed women who reported performing BSEs, CBEs (<40 years of age), and mammographies, regardless of BBD history. CONCLUSIONS: The majority of DES-exposed women receive breast cancer screenings at least at recommended intervals, but over two thirds do not perform monthly BSEs. Future efforts should be focused on further educating this and other at-risk populations through mailed reminders and during patient consultations on the benefits of screening examinations.